2014
DOI: 10.1016/j.chembiol.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Is the Target for the Antibacterial Effects of Nonsteroidal Anti-Inflammatory Drugs

Abstract: Evidence suggests that some nonsteroidal anti-inflammatory drugs (NSAIDs) possess antibacterial properties with an unknown mechanism. We describe the in vitro antibacterial properties of the NSAIDs carprofen, bromfenac, and vedaprofen, and show that these NSAIDs inhibit the Escherichia coli DNA polymerase III β subunit, an essential interaction hub that acts as a mobile tether on DNA for many essential partner proteins in DNA replication and repair. Crystal structures show that the three NSAIDs bind to the sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 50 publications
3
115
0
2
Order By: Relevance
“…Although this finding is considered to result from the anti-inflammatory effects of ibuprofen, it might also be attributable to the antimicrobial effects of ibuprofen, which include blocking of adherence to uroepithelial cells, reduced motility, and reduced toxin and biofilm production, as well as inhibition of growth (9,25,26). Diclofenac and other NSAIDs inhibit bacterial DNA synthesis (10,91) in E. coli; this was shown to be through the inhibition of a DNA polymerase (96).…”
Section: Discussionmentioning
confidence: 99%
“…Although this finding is considered to result from the anti-inflammatory effects of ibuprofen, it might also be attributable to the antimicrobial effects of ibuprofen, which include blocking of adherence to uroepithelial cells, reduced motility, and reduced toxin and biofilm production, as well as inhibition of growth (9,25,26). Diclofenac and other NSAIDs inhibit bacterial DNA synthesis (10,91) in E. coli; this was shown to be through the inhibition of a DNA polymerase (96).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biodegradation of the highest dose of naproxen (15 mg/L) ended with 29% efficiency most likely due to the critical level of inhibitory or toxic metabolites. Recently, more attention has been focused on the antibacterial activity of certain NSAIDs or their derivatives [38,39]. Although the mechanisms of this process are not known, one study found that vedaprofen, bromfenac and carprofen-by binding to polymerase α subunit-inhibit the proliferation of E. coli, A. baylyi, S. aureus and B. subtilis cells [39].…”
Section: Biodegradation Of Different Concentration Of Naproxenmentioning
confidence: 99%
“…Recently, more attention has been focused on the antibacterial activity of certain NSAIDs or their derivatives [38,39]. Although the mechanisms of this process are not known, one study found that vedaprofen, bromfenac and carprofen-by binding to polymerase α subunit-inhibit the proliferation of E. coli, A. baylyi, S. aureus and B. subtilis cells [39]. Inhibitory effect of naproxen on the ammonia oxidizing bacterium (AOB) Nitrosomonas europaea was observed by Wang et al [40].…”
Section: Biodegradation Of Different Concentration Of Naproxenmentioning
confidence: 99%
“…The compound, which also bound to the subunit I of the LM-binding pocket, displayed an IC50 value fo i hi itio of α-β2-binding of 40 µM. In 2014 Oakley and coworkers reported that the weak antibacterial effects of non-steroidal antiinflammatory drugs (NSAIDs) such as (R)-vedaprofen 60, bromfenac 61 or (S)-carprofen 62 (Scheme 22) are due to their binding to the subunit I of the LM-binding pocket of the β-clamp (Yin et al 2014a). …”
Section: In 2008mentioning
confidence: 99%
“…In this context the bacterial replisome machinery, which consists of at least twelve interacting enzymes that are highly conserved in bacteria, is a good structure to target (Robinson et al 2012). Next to the DNA gyrase, which also belongs to the bacterial replisome and has already been discussed, the bacterial DnaN polymerase sliding clamp has recently attracted attention as an antibacterial target (Georgescu et al 2008b;Kjelstrup et al 2013;Wolff et al 2014;Yin et al 2014a;Yin et al 2014b;Holzgrabe 2015;Kling et al 2015;Yin et al 2015). The bacterial DnaN or β-clamp is a ring-shaped homodimer, with each monomer composed of three globular domains, that functions as a crucial subunit of the DNA polymerase III holoenzyme (Scheme 19).…”
Section: Tari Et Al Presented the Pyrrolopyrimidine 34mentioning
confidence: 99%